2012
DOI: 10.1037/a0026483
|View full text |Cite
|
Sign up to set email alerts
|

Beyond shared perceptions of trust and monitoring in teams: Implications of asymmetry and dissensus.

Abstract: Past research has implicitly assumed that only mean levels of trust and monitoring in teams are critical for explaining their interrelations and their relationships with team performance. In this article, the authors argue that it is equally important to consider the dispersion in trust and monitoring that exists within teams. The authors introduce "trust asymmetry" and "monitoring dissensus" as critical dispersion properties of trust and monitoring and hypothesize that these moderate the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 67 publications
4
145
1
Order By: Relevance
“…Unlike the direct and referent-shift consensus models, a dispersion model focuses on differences in the amount of consensus between units, rather than differences in the mean levels between units. In the context of trust, some prior studies have shown that team members do not always agree on their levels of trust as evidenced by statistics that indicate the degree of agreement (Colquitt, LePine, Zapata, & Wild, 2011;De Jong & Dirks, 2011;Gillespie, 2005). In the present research where consensus in trust in leaders concerns the similarity and differences in team members' individual levels of trust in leaders, the dispersion model is most appropriate.…”
Section: Collective Constructs and Consensusmentioning
confidence: 99%
“…Unlike the direct and referent-shift consensus models, a dispersion model focuses on differences in the amount of consensus between units, rather than differences in the mean levels between units. In the context of trust, some prior studies have shown that team members do not always agree on their levels of trust as evidenced by statistics that indicate the degree of agreement (Colquitt, LePine, Zapata, & Wild, 2011;De Jong & Dirks, 2011;Gillespie, 2005). In the present research where consensus in trust in leaders concerns the similarity and differences in team members' individual levels of trust in leaders, the dispersion model is most appropriate.…”
Section: Collective Constructs and Consensusmentioning
confidence: 99%
“…On the one hand, the monitoring literature has framed transparency and trust as alternative and incompatible mechanisms of control (De Jong & Dirks, 2012;Luhmann, 1979;Piccoli & Ives, 2003). On the other hand, it is rather hard to imagine a well-performing environment either of total transparency devoid of trust, or of total trust devoid of transparency (Webber, 2008).…”
Section: Investigating the Culture Of Transparency And The Role Of Trustmentioning
confidence: 99%
“…Team members would also have more responsibility for the tasks they need to complete. They would also obtain more support from one another (De Jong & Dirks, 2012). Not only would job performance be increased but also employees' creativity would also be enhanced (Zhang & Zhou, 2014).…”
Section: Practical Implicationsmentioning
confidence: 99%